Functional morphology of the bovid astragalus in relation to habitat: Controlling phylogenetic signal in ecomorphology. (21st July 2014) - Barr, W. Andrew
ABSTRACT Bovid astragali are one of the most commonly preserved bones in the fossil record. Accordingly, astragali are an important target for studies seeking to predict the habitat preferences of fossil bovids based on bony anatomy. However, previous work has not tested functional hypotheses linking astragalar morphology with habitat while controlling for body size and phylogenetic signal. This article presents a functional framework relating the morphology of the bovid astragalus to habitat‐specific locomotor ecology and tests four hypotheses emanating from this framework. Highly cursorial bovids living in structurally open habitats are hypothesized to differ from their less cursorial closed‐habitat dwelling relatives in having (1) relatively short astragali to maintain rotational speed throughout the camming motion of the rotating astragalus, (2) a greater range of angular excursion at the hock, (3) relatively larger joint surface areas, and (4) a more pronounced "spline‐and‐groove" morphology promoting lateral joint stability. A diverse sample of 181 astragali from 50 extant species was scanned using a Next Engine laser scanner. Species were assigned to one of four habitat categories based on the published ecological literature. A series of 11 linear measurements and three joint surface areas were measured on each astragalus. A geometric mean body size proxy was used to size‐correct the measurement data. Phylogenetic generalized least squares (PGLS) was used to test for differences between habitat categories while controlling for body size differences and phylogenetic signal. Statistically significant PGLS results support Hypotheses 1 and 2 (which are not mutually exclusive) as well as Hypothesis 3. No support was found for Hypothesis 4. These findings confirm that the morphology of the bovid astragalus is related to habitat‐specific locomotor ecology, and that this relationship is statistically significant after controlling for body size and phylogeny. Thus, this study validates the use of this bone as an ecomorphological indicator. J. Morphol. 275:1201–1216, 2014. © 2014 Wiley Periodicals, Inc.